Plasma urate, lung function and chronic obstructive pulmonary disease: a Mendelian randomisation study in 114 979 individuals from the general population. Issue 8 (29th November 2017) - Kobylecki, Camilla J; Vedel-Krogh, Signe; Afzal, Shoaib; Nielsen, Sune F; Nordestgaard, Børge G
Abstract : Background: Urate is a strong antioxidant in plasma and may protect against lung function impairment. We tested the hypothesis that high plasma urate is causally associated with better lung function and low risk of respiratory symptoms and COPD. Methods: We measured lung function and plasma urate in 114 979 individuals from the Copenhagen City Heart Study and the Copenhagen General Population Study and genotyped for SLC2A9 rs7442295 and ABCG2 rs2231142 variants, previously associated with high plasma urate, in 110 152 individuals. Results: In the two studies combined, multivariable-adjusted 100 µmol/L higher plasma urate was associated with −1.54% (95% CI −1.67 to −1.40) lower FEV1 % predicted and −1.57% (95% CI −1.69 to −1.44) lower FVC % predicted observationally; the corresponding estimates for genetically determined 100 µmol/L higher plasma urate were −0.46% (95% CI −1.17 to 0.25) and −0.40% (95% CI −1.03 to 0.23). High plasma urate was also associated with higher risk of respiratory symptoms; however, genetically determined high plasma urate was not associated with respiratory symptoms. Finally, we identified 14 151 individuals with COPD and found ORs of 1.08 (95% CI 1.06 to 1.11) for COPD observationally and 1.01 (95% CI 0.88 to 1.15) genetically per 100 µmol/L higher plasma urate. Conclusion: High plasma urate was associated with worse lung function and higher risk of respiratory symptoms and COPD in observational analyses; however, genetically high plasma urate was not associated with any of these outcomes. Thus, our data do not support a direct causal relationship.